Hydrogen atom abstraction pathways to functionalised free radicals - Lush, R (2001)
﻿ Radical translocation chemistry has classically been employed for the generation of carboncentred radicals as a means of remotely functionalising nominally unreactive sites. Previous work within the group had investigated vinyl radicals to effect translocation and had identified a need for a more reactive abstracting radical. In this regard, the high energy of alkoxyl radicals would facilitate rapid 1,5-hydrogen abstraction as opposed to simple reduction. This thesis describes the use of alkoxyl radicals, generated from N-alkoxyphthalimides, to abstract a hydrogen atom selectively from the α-position of a lactam ring. Alkoxyl radicals generated from precursors designed to lead to intramolecular trapping of the translocated radical were prone to β-scission in preference to 1,5-hydrogen atom abstraction. This is attributed to a combination of developing π-overlap in the transition state and stabilisation of the resulting radical both by nitrogen and the attached alkyl substituents. Incorporation of an alkenyl trap onto the lactam ring led to successful 1,5-hydrogen atom abstraction and stereoselective cyclisation, although β-scission remained the dominant pathway. Translocation initiated by nitrogen-centred radicals was investigated and it was found that 1,5-hydrogen abstraction occurred in preference to β-scission; intramolecular trapping of the translocated radical proved impossible either because the precursors were unstable to the reaction conditions or because increased steric bulk impeded hydrogen abstraction by the less reactive aminyl radical. Preparation of bicyclic pyrrolidinones via successive 5-endo-5-exo-trig cyclisations was investigated; the precursors were found to undergo direct reduction in preference to cyclisation. Alkyl or aryl groups attached to the a-acylamino carbon may lead to preferential 5-endo cyclisation by stabilisation of the developing radical in the transition state.